Clinical characteristics of pulmonary Mycobacterium scrofulaceum disease in 2001–2011: A case series and literature review. Issue 9 (September 2016) - Suzuki, Shoji; Morino, Eriko; Ishii, Makoto; Namkoong, Ho; Yagi, Kazuma; Asakura, Takanori; Asami, Takahiro; Fujiwara, Hiroshi; Uwamino, Yoshifumi; Nishimura, Tomoyasu; Tasaka, Sadatomo; Betsuyaku, Tomoko; et al.
Abstract: Background: Mycobacterium scrofulaceum is a well-known pathogen associated with cervical lymphadenitis in children. However, pulmonary M. scrofulaceum disease is a rare condition with unknown clinical features. The present study aimed to clarify the clinical features of pulmonary M. scrofulaceum disease described in recent cases and reports. Methods: We reviewed the medical records of all adult patients with pulmonary M. scrofulaceum disease at Keio University Hospital and the National Center for Global Health and Medicine Center Hospital between 2001 and 2011. We also conducted a review of the PubMed database to identify additional cases of pulmonary M. scrofulaceum disease in adults. Results: Our study identified 8 cases of pulmonary M. scrofulaceum disease at the 2 identified institutions during our study period. Most cases were diagnosed in middle-aged and elderly men with underlying pulmonary diseases such as chronic obstructive pulmonary disease and Mycobacterium avium complex lung disease, as well as those with a history of pulmonary tuberculosis. In contrast, most previously reported cases identified through our literature review had a history of dust inhalation or underlying silicosis. Three of 8 cases at our institutions and 20 of 23 cases from the literature were treated with combination therapies. Conclusions: We conclude that in the recent histories of our institutions, pulmonary M. scrofulaceum disease has mainly occurred in patients with chronic pulmonary diseases. We further conclude that combination therapies that include clarithromycin might yield better patient outcomes.